1998
DOI: 10.1542/peds.102.5.e51
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Trial of Ibuprofen Syrup Administered During Febrile Illnesses to Prevent Febrile Seizure Recurrences

Abstract: ABSTRACT. Objectives. Febrile seizures recur frequently. Factors increasing the risk of febrile seizure recurrence include young age at onset, family history of febrile seizures, previous recurrent febrile seizures, time lapse since previous seizure <6 months, relative low temperature at the initial seizure, multiple type initial seizure, and frequent febrile illnesses. Prevention of seizure recurrences serves two useful purposes: meeting parental fear of recurrent febrile seizures in general and reducing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(63 citation statements)
references
References 31 publications
1
57
0
5
Order By: Relevance
“…As with acetaminophen, ibuprofen also has been shown to be ineffective in preventing recurrence of febrile seizures. [33][34][35] In general, acetaminophen and ibuprofen are considered to be safe and effective antipyretics for children. However, hepatotoxicity (with acetaminophen) and respiratory failure, metabolic acidosis, renal failure, and coma (with ibuprofen) have been reported in children after overdose or in the presence of risk factors.…”
Section: Benefits and Risks Of Intermittent Antipyreticsmentioning
confidence: 99%
“…As with acetaminophen, ibuprofen also has been shown to be ineffective in preventing recurrence of febrile seizures. [33][34][35] In general, acetaminophen and ibuprofen are considered to be safe and effective antipyretics for children. However, hepatotoxicity (with acetaminophen) and respiratory failure, metabolic acidosis, renal failure, and coma (with ibuprofen) have been reported in children after overdose or in the presence of risk factors.…”
Section: Benefits and Risks Of Intermittent Antipyreticsmentioning
confidence: 99%
“…This, and the rarity of febrile convulsions, may be why studies to date have not demonstrated any beneficial effect of antipyretics on febrile convulsions. 43,[55][56][57][58] Given their infrequency and the difficulties of ensuring compliance with study medications over a prolonged period of time in the community, it seems unlikely that a large enough study will ever be funded to investigate this relationship further, and alternative study designs may have to be used, such as ecological studies.…”
Section: Evidence That Antipyretics Prevent Febrile Convulsionsmentioning
confidence: 99%
“…It is known that aggressive antipyretics are not helpful (5). Anticonvulsants such as phenobarbital may help but have significant potential adverse effects (6).…”
Section: Commentarymentioning
confidence: 99%